PREFACE (Религиски дијалог и соработка, 2025)
The human awareness of social appertaining has deep biological and social roots. The alienatedindividual, on his own, is of no significance and is not a human in the real sense of the word, unlesshe becomes a member of any group, reaches a social position and his own place within the system ofrelationships. In contrast to the political parties, which are a relatively new phenomenon, the religiosityrepresents a universal social phenomenon. Hardly any civilization of significance does not have a certainreligious component incorporated within itself or has not been based on it.Evaluating the claims of the secularization story, we face several unresolved questions:1. Is the suppression of religion limited to the area of Europe and is the narrative of secularization atthe same time an attempt to present the European experience to the rest of the world.2. Are religious beliefs being comprehensively suppressed and people becoming less religious, orare we dealing with new forms of religiosity, where new models of religious beliefs and practices areemerging that replace the old/traditional ones?3. Has the religiosity of people not decreased and what has been achieved with the process of secularization.Is this a change in the social role of religion? Secularism is not the suppression of religion butan aspect of the weakening of religious authority.